FAKTOR – FAKTOR YANG MEMPENGARUHI SERAPAN ANGGARAN PADA DINAS PEKERJAAN UMUM KOTA PAREPARE - Jumriani, Jumriani (Economos : Jurnal Ekonomi dan Bisnis, 2018)
This studyentitled ?Analysis of Factors Affecting the Low Budget Absorption at the Public Works Office of the Parepare City?. This study aims to examine the effect of planning documents, administrative records, human resources, and inventory money on the absorption of the budget at the Public Works Office of the Parepare City. Data collection techniques used in this study is interviews, documentation and questionnaires. The population in this study was as crowded as employees at the Public Works Agency, which amounted to 60 respondents. This study uses multiple linear regression analysis. The results of this study indicate that planning documents, administrative records, human resources, and inventory money have a significant effect on budget absorption of 63.9% and the remaining 36.1% is influenced by other factors not included in this study.As for other factors that influence namely procurement documents, procurement of goods and services, regulations and factor tenders or auctions. Variables that have more influence on budget absorption are planning documents.